Pre-Signal and Influencing Sources of the Extreme Cold Surges at the Beijing 2022 Winter Olympic Competition Zones - Ting Ding; Hui Gao; Yuan Yuan (Atmosphere, 2020)
The 24th Olympic and Paralympic Winter Games will take place in Beijing in 2022. All three competition zones are vulnerable to extreme cold surges (ECSs), owing to the occurrence of the East Asian winter monsoon. In this paper, a representative competition domain (37.5–42.5° N, 110–120° E) is adopted, with a view to avoiding the differences in both the geographies and the thresholds of ECSs among different zones by considering the probability of simultaneous occurrences. Since 2009, the ECSs in the domain have displayed higher frequency and extremity. Based on all ECS cases in the domain, the dominant circulation is revealed by a quasi “reverse-Ω” pattern, with two strong ridges over the east of the Ural Mountain and the Okhotsk Sea, and a broad, deep trough in East Asia. The influencing sources of the ECSs at the domain could be traced to the Novaya Zemlya by a day-by-day backward analysis. The oblique latitude/longitude–time profiles of both the 500 hPa geopotential height and the 850 hPa air temperature anomalies from the source to the domain clearly indicate that the pre-signal could have a leading influence that exceeds ten days, with a slow accumulation in the first stage and a rapid outburst in the second stage.